A high-energy-density and long-stable-performance zinc-air fuel cell system. (1st May 2019) - Pei, Pucheng; Huang, Shangwei; Chen, Dongfang; Li, Yuehua; Wu, Ziyao; Ren, Peng; Wang, Keliang; Jia, Xiaoning
Highlights: The main cause of the voltage decay of zinc-air fuel cell at high current density is validated. Isolate ZnO precipitations from the electrolyte solution. Optimize the flow field to suppress anode passivation at high current density. A zinc-air fuel cell system has achieved the highest electrolyte capacity of 1025 Ah L −1 to date. The optimization strategy can be generalized to other metal-air fuel cells with aqueous electrolytes. Abstract: Metal-air fuel cells are regarded as potential alternatives of power supply due to their high specific energy. However, the excessive accumulation of reaction products leads to performance degradation, low energy density, and short service life, hampering more widespread application. This study focuses on enormously increasing the fuel cell system energy density by electrolyte isolation and management. Filters are used to isolate metal oxide (including ZnO, MgO, and Al2 O3 ) from supersaturated electrolyte solutions in fuel cells. The filtration efficiency is close to 100%. The flow field is optimized to suppress the anode passivation. In zinc-air fuel cells (ZAFCs), the ratio of discharge capacity to electrolyte volume (electrolyte capacity) is up to 1025 Ah L −1, and the discharging voltage still remains stable. The zinc-air fuel cell system (ZAFCS) exhibits high energy density, high stability, and low cost, rendering this type of metal-air fuel cell a promising energy storage in electric vehicles.